The Effects of Fiddler Crabs (Uca sp) on C/N Ratio and Redox Potential of Soil in Mangrove Ecosystems - Mulyanto Mulyanto; Herwati Umi (Research Journal of Life Science, 2016)
Research has been done in Ketapang mangrove area of  Probolinggo city in months of September-November 2015. The objectives are to observe the fiddler crab community stucture and to analyze the effects of fiddler crabs on C/N ratio and redox potential of soil in mangrove ecosystems. The samples of fiddler crabs were taken during the low tides at 4 station (20 transects with sizes of 1 m2). Data of the fiddler crabs were measured from the soil digging insides the transect. The soil samples were taken from these crab holes wall (at the surface and at the depth of 20 cm), under the holes at the depth of 40 cm as well as from the locations that undwells by these animals at the same depth. The fiddler crab identified are U. Triangularis between 2 – 6 ind/m2, U paradussumieri 1 – 3 ind/m2, U perplexa 14 – 32 ind/m2, U dussumieri 12 – 27 ind/m2 and U. Tetragonon 3 – 6 ind/m2. The diversity is moderate (H = 1.7) and the dominance index was low (C = 0.37). C/N ratio soil were inhabited by fiddler crab between 6 – 14, the undwelled area were 14 – 20. Soil C/N ratio was inhabited by the fiddler crab at the surface and depth of 20 cm in average of 9 cm while at 40 cm in avergae of 12. The low of C/N ratio at surface and depth of 20 cm causing the organic matter turnover faster because the high nitorgen content. Soil potential redox (Eh) the undwelled areas was found –0.647 mV, meanwhile the soil Eh in the dwelled areas was positive (0.68 till 0.87 mV). This mean, the decpmposition was occured during aerobic condition and will produce untoxic subtances.